The Effects of Sodium Hypochlorite on Organic Matters: Influences of Concentration, Renewal Frequency and Contact Area - Aline, Krah-Sinan Akissi; Adou-Assoumou, Marie; Djolé, Stéphane Xavier; Diemer, Franck; Gurgel, Marie (Iranian Endodontic Journal, 2020)
Introduction: Sodium hypochlorite (NaOCl) reacts mainly with proteins and its effectiveness depends on the substances chemical reactivity. It has been reported that volume, concentration, renewal, time, temperature and contact area affect the diffusion of NaOCl in the root canal. However, the relationship between some of these factors is not clear. The purpose of this study was to test the effect of volume, contact area, concentration and renewal frequency of 2.5% and 9.8% NaOCl solutions on their organic matter dissolving-capacity. Methods and Materials: Pieces of gelatine (18% w/v) with standardized weight, form and structure were either fully or partially exposed to a 2.5% or 9.8% NaOCl solution. In three successive studies, biological dissolution-capacity of NaOCl was tested under different conditions. In experiment 1 the effect of volume/time, in experiment 2 the time/concentration/renewal frequency and in experiment 3 the contact area/renewal frequency/concentration/time of 2.5% or 9.8% NaOCl solutions on dissolving-capacity of organic matter were studied. The weight loss of gelatine pieces over time was registered. The non-parametric tests of Mann-Whitney and Kruskal-Wallis at the 5% threshold were used for statistical analysis. Results: The differences between the two concentrations of NaOCl solution (2.5% and 9.8%) are statistically significant in the effects of different volumes on total dissolution time (P<0.05). Differences in weight loss according to the concentration of the NaOCl solution used (2.5% or 9.8%) were significant after 2 min of contact time (P<0.05). Differences in weight loss between the model and the tube are significant (P<0.05) when the solution is repeated every 30 sec and every 1 min after 2 min of contact. Conclusion: This in vitro study showed that using a more concentrated NaOCl solution would certainly improve the endodontic disinfection, but the biological risk in case of apical extrusion should be considered. Keywords: Concentration; Dosage; Gelatine; Root Canal Irrigant; Sodium Hypochlorite